The CGIAR at a crossroads: assessing the role of international agricultural research in poverty alleviation from an innovation systems perspective - Ekboir, Javier M. (2009)
Globalization, technical change and migration are changing the dynamics of poverty and food production. These factors, combined with a better understanding of the nature of complex processes, are also changing the nature of scientific research, the roles researchers can play in poverty alleviation and the niches in which the CGIAR can operate. While keeping strong breeding and research programs, the CGIAR should devote increasing resources to better characterize the dynamics of poverty, redefine the networks it will use to promote the use of scientific information to foster innovation, link local innovators and researchers with international scientific networks, and help to build innovative capabilities in developing countries. These capabilities should refer not only to scientific research but also to new ways to support innovation and to design and implement poverty-alleviation programs. Finally, CGIAR researchers should adopt new research methods to better integrate into local and international innovation networks.